(untitled) (IAHS Medical Journal, 2022)
Background: Coronavirus disease 2019 (COVID -19) is a major global health problem. During this pandemic situation, adolescent groups in low-income and middle-income countries become at high risk which crucially affected their physical and mental health. The aim of this study determine the effect of challenges students faced on blended learning, disharmony of economic conditions during the pandemic situation. Materials and methods: A descriptive cross-sectional study was carried out to assess the impacts of coronavirus infection on adolescence during the COVID-19 pandemic among the 393 school-going adolescents by a semistructured questionnaire in a selected school of Cumilla. Results: Among the respondent adolescents, two-thirds of them (66.2%) belonged to the middle adolescence group, the majority came from urban areas (88.3%) and middle-income families (77.9%). The majorities were responded about the proper use of mask (94.4%), frequent hand washing with soap-water or sanitizer for 20 seconds (98.0%), avoiding crowded places (98.1%) and maintenance of social distancing (89.6%). Cough (96.2%), Fever (95.7%) and Dyspnoea (86.0%) were cited as common symptoms of coronavirus infection. Nearly one-out-of-three adolescents (30.5%) never faced any problem and one-out-of-five adolescents (18.9%) mentioned problem faced by them. Conclusion: Nearly one-third of adolescents never faced any problem during the COVID-19 pandemic and the rest faced problems that ranged occasional to always. The study findings also suggested that adolescents from middle socioeconomic status had a good perception and practices towards COVID-19 infection. IAHS Medical Journal Vol 5(1), June 2022; 3-7